Executive Functions and Morphosyntax: Distinguishing DLD From ADHD in French-Speaking Children - Stanford, Emily; Delage, Hélène (Frontiers in Psychology, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is commonly associated with deficits in executive functions (EFs), but children with this disorder frequently demonstrate co-occurring morphosyntactic impairment when assessed using standardized tests. On the other hand, children with Developmental Language Disorder (DLD), a population defined by impaired linguistic functioning, are often diagnosed with comorbid EF deficits. We investigated EF and morphosyntax in 60 French-speaking children aged six to 12: 20 with typical development (TD), 20 with ADHD, 20 with DLD. To obtain an EF profile for the different cognitive groups, we used standardized tests to assess lower-order EF skills, (i) selective attention and (ii) short-term memory capacity, and higher-order EF skills, (i) working memory capacity and (ii) attention shifting. To test morphosyntax, we used (i) a standardized omnibus test of morphosyntax that elicited a variety of complex structures and (ii) a more fine-grained probe test that assessed the production of third person object clitic pronouns, a clinical marker of DLD in French. Children with ADHD and DLD were associated with different EF and morphosyntactic profiles: children in the ADHD group demonstrated higher-order EF weakness and difficulty on the omnibus morphosyntax task, whereas children with DLD showed both lower- and higher-order limitations and struggled with both morphosyntax tasks. Our findings indicate that deficits in morphosyntax are not characteristic of ADHD but that the performance of children with ADHD can mimic morphosyntactic impairment when all-encompassing omnibus tests that evaluate various and unpredictable structures are used. If morphosyntax is tested using reliable markers of atypical language development and external cognitive-load factors are optimally reduced, there are significant discrepancies in the observed ADHD-DLD outcomes. Clinical implications that include perspectives for the differential diagnosis of ADHD and DLD are discussed.